The Way of the 88 Temples : Journeys on the Shikoku Pilgrimage - Sibley, Robert C. (Robert Cameron), 1951- (Book collections on Project MUSE., 2013)
The Henro Michi is one of the oldest and most famous pilgrimage routes in Japan. It consists of a circuit of eighty-eight temples around the perimeter of Shikoku, the smallest of Japan's four main islands. Every henro, or pilgrim, is said to follow in the footsteps of Kōbō Daishi, the ninth-century ascetic who founded the Shingon sect of Buddhism. Over the course of two months, the author walked this 1,400-kilometer route (roughly 870 miles), visiting the sacred sites and performing their prescribed rituals.